Seasonal observations of OH and HO2 in the remote tropical marine boundary layer - Z. L. Fleming (Atmospheric Chemistry and Physics, 2012)
Field measurements of the hydroxyl radical, OH, are crucial for our understanding of tropospheric chemistry. However, observations of this key atmospheric species in the tropical marine boundary layer, where the warm, humid conditions and high solar irradiance lend themselves favourably to production, are sparse. The Seasonal Oxidant Study at the Cape Verde Atmospheric Observatory in 2009 allowed, for the first time, seasonal measurements of both OH and HO2 in a clean (i.e. low NOx), tropical marine environment. It was found that concentrations of OH and HO2 were typically higher in the summer months (June, September), with maximum daytime concentrations of ~9 × 106 and 4 × 108 molecule cm−3, respectively – almost double the values in winter (late February, early March). HO2 was observed to persist at ~107 molecule cm−3 through the night, but there was no strong evidence of nighttime OH, consistent with previous measurements at the site in 2007. HO2 was shown to have excellent correlations (R2 ~ 0.90) with both the photolysis rate of ozone, J(O1D), and the primary production rate of OH, P(OH), from the reaction of O(1D) with water vapour. The analogous relations of OH were not so strong (R2 ~ 0.6), but the coefficients of the linear correlation with J(O1D) in this study were close to those yielded from previous works in this region, suggesting that the chemical regimes have similar impacts on the concentration of OH. Analysis of the variance of OH and HO2 across the Seasonal Oxidant Study suggested that ~70% of the total variance could be explained by diurnal behaviour, with ~30% of the total variance being due to changes in air mass.